THE EVALUATION OF ENGLISH PROFESSIONALLY-ORIENTED COMPETENCE IN SPEAKING OF PROSPECTIVE PEDIATRICIANS - Khrystyna Tsymbrovska (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The problem of evaluation of English professionally-oriented competence in speaking in the context of buiding the mentioned competence in prospective pediatricians. The interaction between evaluation, measurement and testing is defined. The experience of American and European scientists concerning the evaluation of English professionally-oriented competence in speaking is analysed. The categories of linguodidactic tests and types of tests to measure the level of English professionally-oriented competence in speaking of prospective pediatricians. The main stages of test designing are outlined. The levels of competence and evaluation criteria of professionally-oriented competence in speaking of prospective pediatricians are determined. The key features of effectivness of communicative tests are established.